2014
DOI: 10.1007/s00775-014-1197-3
|View full text |Cite
|
Sign up to set email alerts
|

Sulfite-oxidizing enzymes

Abstract: Sulfite oxidizing enzymes are essential mononuclear molybdenum (Mo) proteins involved in sulfur metabolism of animals, plants and bacteria. There are three such enzymes presently known: (1) sulfite oxidase (SO) in animals, (2) SO in plants, and (3) sulfite dehydrogenase (SDH) in bacteria. X-ray crystal structures of enzymes from all three sources (chicken SO, Arabidopsis thaliana SO, and Starkeya novella SDH) show nearly identical square pyramidal coordination around the Mo atom, even though the overall struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 103 publications
2
60
0
2
Order By: Relevance
“…In C. albicans, there are no known enzymes that convert toxic sulfite to nontoxic sulfate, such as sulfite oxidase, an enzyme that occurs in humans, bacteria, and plants (Kappler and Enemark 2015). Therefore, C. albicans controls the levels of excess toxic sulfite produced in a different way.…”
Section: Discussionmentioning
confidence: 99%
“…In C. albicans, there are no known enzymes that convert toxic sulfite to nontoxic sulfate, such as sulfite oxidase, an enzyme that occurs in humans, bacteria, and plants (Kappler and Enemark 2015). Therefore, C. albicans controls the levels of excess toxic sulfite produced in a different way.…”
Section: Discussionmentioning
confidence: 99%
“…Many workers enjoyed and profited from exchanges, sabbaticals, collaborations and conference interactions with Enemark and these greatly assisted the ongoing development of the field. Enemark and co‐workers went on to make major contributions to our understanding of SO and related enzymes , …”
Section: Brief Historical Perspectivementioning
confidence: 99%
“…The corresponding structures deduced from electron spin echo (ESE) experiments on these forms, in conjunction with isotopic labeling, density functional theory (DFT) calculations, 9,10 and Please do not adjust margins Please do not adjust margins studies of model compounds, are shown on the right hand side of Figure 3. 11 Elucidation of the specific structures associated with the various CW EPR spectra has been especially challenging because the Mo(V) coordination sphere involves only O and S atoms, whose primary isotopes ( 16 O and 32 S) are magnetically silent (I = 0). Determining whether the solvent-exposed, exchangeable equatorial ligand is an O, OH − , H 2 O, SO 3 2− , or SO 4 2− group, has required isotopic labeling with 17 O (I = 5/2) or 33 S (I =3/2) in order to obtain experimental hyperfine interaction (hfi) and nuclear quadrupole interaction (nqi) constants for these coordinated nuclei using variable-frequency high resolution pulsed EPR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%